(untitled) (Iraqi Journal of Medical Sciences, 2004)
Aim: To evaluate right and left ventricular function in patients with chronic lung disease by echocardiography Patients & methods: 50 patients with different chronic lung disease (obstructive, restrictive and vascular lung disease) admitted to the teaching hospital / Iraqi medical college were evaluated by clinical examination and investigations (Chest x-ray, ECG, Echocardiography and Pulse oximetry) to assess the right and left ventricular function in relation to chronic lung disease. Results: The results in this study showed that 40 patients had obstructive lung disease, 7 patients had restrictive lung disease and 3 patients had vascular lung disease. 100% of the patients with vascular lung disease, 65% of the patients with obstructive lung disease and 42% of the patients with restrictive lung disease were diagnosed with right ventricular dysfunction which was inversely related to O2 saturation LV dysfunction was rarely diagnosed in patients with chronic lung disease. It was also found that 59% of the patients diagnosed with RV dysfunction by echocardiography had shown ECG criteria of RVH on ECG examination. Conclusion: Right ventricular dysfunction is common in patients with second stage chronic lung disease especially when O2 saturation is >90%, the presence of left ventricular dysfunction is related to RV dysfunction through ventricular interdependence. Keywords: Right and left ventricular dysfunction, chronic lung disease, Echocardiography. Iraqi J Med Sci, 2004, Vol. 3 (1): 22-25